Pengaruh PENGARUH AKUNTANSI BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN (2019-2023): PENGARUH AKUNTANSI BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN (2019-2023) - Maryani, Eni; Haitamy, Ery Bestari Al; Saputra, Ferdyan Wana (LP2M Politeknik Jambi, 2025)
Increasing company performance means increasing shareholder wealth, which has often been the focus of previous research. Company performance is investors' perception of the company. This research aims to determine the effect of environmental cost accounting on company financial performance. The company's financial performance is proxied by the Return on Assets (ROA) indicator. Furthermore, the research year focuses only from 2019- 2023. The results of hypothesis testing using SPSS show that the partial significance value for the environmental cost accounting variable is 0.145 > 0.05, which means that environmental cost accounting has no effect on the company's financial performance. So it can be concluded that H0 is accepted and Ha is rejected.